On coefficient functional and Bohr-radius for some classes of analytic functions - Palani, Jeyaraman Muthusamy; Raman, Parvatham; Habibullah, Aaisha Farzana (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We examine sharp bounds of coefficient functionals, such as Zalcman functional, second-order Hankel determinant, and third-order Toeplitz and Hermitian–Toeplitz determinants for the class of analytic functions. Growth estimates and bounds for the difference of successive coefficients are  determined. Further, by using growth estimates,  we obtain the Bohr radius and the Bohr–Rogosinski phenomenon.